Activation of Extracellular Signal-Regulated Kinase 5 Reduces Cardiac Apoptosis and Dysfunction via Inhibition of a Phosphodiesterase 3A/Inducible cAMP Early Repressor Feedback Loop - Yan, Chen (2007)
Substantial evidence suggests that the progressive loss of cardiomyocytes caused by apoptosis significantly contributes to the development of heart failure. β-Adrenergic receptor activation and subsequent persistent phosphodiesterase 3A (PDE3A) downregulation and concomitant inducible cAMP early repressor (ICER) upregulation (PDE3A/ICER feedback loop) has been proposed to play a key role in the pathogenesis of cardiomyocyte apoptosis. In contrast, insulin-like growth factor-1 can activate cell survival pathways, providing protection against cell death and restoring muscle function. In this study, we found that insulin-like growth factor-1 activates extracellular signal-regulated kinase 5 (ERK5) and inhibits PDE3A/ICER feedback loop. Insulin-like growth factor-1 normalized isoproterenol-mediated PDE3A downregulation and ICER upregulation via ERK5/MEF2 activation, and also inhibited isoproterenol-induced myocyte apoptosis. To determine the physiological relevance of ERK5 activation in regulating PDE3A/ICER feedback loop, we investigated the PDE3A/ICER expression and cardiomyocyte apoptosis in transgenic mice with cardiac specific expression of a constitutively active form of mitogen-activated protein (MAP)/extracellular signal-regulated protein kinase (ERK) kinase 5α (MEK5α) (CA-MEK5α-Tg). In wild-type mice, pressure overload– or doxorubicin-induced significant reduction of PDE3A expression and subsequent ICER induction. Cardiac specific expression of CA-MEK5α rescued pressure overload– or doxorubicin-mediated PDE3A downregulation and ICER upregulation and inhibited myocyte apoptosis as well as subsequent cardiac dysfunction in vivo. These data suggest that preventing the feedback loop of PDE3A/ICER by ERK5 activation could inhibit progression of myocyte apoptosis as well as cardiac dysfunction. These data suggest a new therapeutic paradigm for end stage of heart failure by inhibiting the PDE3A/ICER feedback loop via activating ERK5.